The “Chapultepec Nature and Culture” project in Mexico City: the citizen dispute between environmental conservation and the “democratization of public space” - MORALES GUZMÁN, Jesús (Utopía y Praxis Latinoamericana, 2023)
This article examines the citizen dispute around the “Chapultepec Nature and Culture” project in Mexico City, based on the literature on megaprojects and the urban extractivism approach, which allows us, on the one hand, to identify possible impacts of the megaproject. and the real estate and commercial logic that occurs in large cities. Using a methodology based on the triangulation of sources, we explore the meaning that the actors of the conflict in certain urban situations attribute to the megaproject (Pérez: 2013 and 2017: and Morales: 2017) and its possible impacts in terms of use. and enjoyment of public space for commercial and commercial purposes as well as the vulnerability and threats in environmental, urban and suburban areas.